Employment and labour market vulnerabilities during COVID-19: The case of Romania - Luminita Chivu; George Georgescu (Romanian Academy, National Institute for Economic Research, 2021)
The extremely fragile balance of the Romanian labour market is severely affected by the crisis caused by the COVID-19 pandemic and by the sudden and almost general deterioration of the macroeconomic context and the business environment. The present study aims to argue that, in times of crisis, such as the current one, the labour market policies need to be varied but also synergistic, in order to stimulate employment and capitalize the potential of each category, so as to contribute to the recovery of the country's macroeconomic and financial framework. Despite the Government's anti-crisis and economic support measures, in the short term, the Romanian labour market is facing the unemployment rate increase, at least in 2020, as a result of the restrictions in many activities, exacerbating the vulnerabilities of the employed population structure described in the study. The analyses carried out revealed that, in Romania, the crisis affected practically all the members of society, but in a disproportionate manner, the most exposed being the vulnerable groups, namely people in the "grey" or informal area of the economy, those working in the most affected sectors and workers with low qualification, many deprived of the needed protection and social assistance. In the context of efforts to identify ways to reduce the distortions generated by the crisis, the integration of social security systems with social assistance can be a viable solution. As activities resume, the labour market tensions are expected to be mitigated both by labour market-specific measures, including those presented in the study, and at the macroeconomic level, adapted to the post-COVID-19 restructuring of the economy, with the necessary policy support at central and local level, including in terms of employment.
Keywords: E24; F66; J10; J21; J46; O15; 330; labour market; COVID-19 pandemic; employment; vulnerable groups; protection and social assistance; macroeconomic risks